The Natural Anthraquinone Parietin Inactivates Candida tropicalis Biofilm by Photodynamic Mechanisms - Juliana Marioni; Bianca C. Romero; Ma. Laura Mugas; Florencia Martinez; Tomas I. Gómez; Jesús M. N. Morales; Brenda S. Konigheim; Claudio D. Borsarelli; Susana C. Nuñez-Montoya (Pharmaceutics)
Background/Objectives: Parietin (PTN), a blue-light absorbing pigment from Teloschistes spp. lichens, exhibit photosensitizing properties via Type I (superoxide anion, O2•−) and Type II (singlet oxygen, 1O2) mechanisms, inactivating bacteria in vitro after photoexcitation. We evaluate the in vitro antifungal activity of PTN against Candida tropicalis biofilms under actinic irradiation, its role in O2•− and 1O2 production, and the cellular stress response. Methods: Minimum inhibitory concentration (MIC) of PTN was determined in C. tropicalis NCPF 3111 under dark and actinic light conditions. Biofilm susceptibility was assessed at MIC/2, MIC, MICx2, MICx4, and MICx6 in the same conditions, and viability was measured by colony-forming units. Photodynamic mechanisms were examined using Tiron (O2•− scavenger) or sodium azide (1O2 quencher). O2•− production was measured by the nitro-blue tetrazolium (NBT) reduction and nitric oxide (NO) generation by Griess assay. Total antioxidant capacity was studied by FRAP (Ferrous Reduction Antioxidant Potency) assay and superoxide dismutase (SOD) activity by NBT assay. Results: Photoexcitation of PTN reduced C. tropicalis biofilm viability by four logs at MICx2. Sodium azide partially reversed the effect, whereas Tiron fully inhibited it, indicating the critical role of O2•−. PTN also increased O2•− and NO levels, enhancing SOD activity and FRAP. However, this antioxidant response was insufficient to prevent biofilm photoinactivation. Conclusions: Photoinactivation of C. tropicalis biofilms by PTN is primarily mediated by O2•−, with a minor contribution from 1O2 and an imbalance in NO levels. These findings suggest PTN is a promising photosensitizer for antifungal photodynamic therapy.